POWER PLAYERS: DO PENSION FUNDS DRIVE STOCK MARKET GROWTH IN THE EUROPEAN UNION? - MILOȘ LAURA RAISA; MILOȘ MARIUS CRISTIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This study investigates the role of pension fund assets (PFA) in driving stock market development across the European Union from 2005 to 2022, using market capitalization as % in GDP as a proxy for stock market growth. Employing a fixed-effects model, we examine the impact of PFA alongside several key economic controls, including domestic credit to the private sector, GDP growth, inflation, gross domestic savings, trade openness, and foreign direct investment inflows. Our findings reveal a strong, positive, and statistically significant relationship between PFA and market capitalization. Specifically, a one-unit increase in pension fund assets is associated with a 0.574 percentage point increase in market capitalization as a share of GDP, underscoring the role that pension funds play in enhancing stock market activity and liquidity.Among the control variables, domestic credit to private sector by banks, GDP growth and gross domestic savings exhibit significant positive effects, suggesting that financial and economic expansion and higher savings rates support stock market growth by improving market liquidity and boosting investor confidence. Inflation also shows a positive association with market capitalization, suggesting that moderate inflation may reflect economic dynamism, thereby attracting investment. Conversely, trade openness has a negative relationship with market capitalization, potentially reflecting increased exposure to external economic shocks or capital outflows. Foreign direct investment, while showing a small positive effect, is not statistically significant.Overall, these findings highlight the importance of pension funds in fostering stock market growth and provide policymakers with insights into strategies for financial development in the EU.